Boswellia serrata has Beneficial Anti‐Inflammatory and Antioxidant Properties in a Model of Experimental Colitis. (12th March 2014) - Hartmann, Renata Minuzzo; Fillmann, Henrique Sarubbi; Morgan Martins, Maria Isabel; Meurer, Luise; Marroni, Norma Possa
<x xml:space="preserve">Abstract</x> Ulcerative colitis is an inflammatory disease that involves only the colon and rectum, being characterized by leukocyte infiltrate and superficial ulcers in the intestinal mucosa. To evaluate the anti‐inflammatory and antioxidant effects of extract from the Boswellia serrata plant in an experimental rat model of acute ulcerative colitis induced by the administration of acetic acid (AA). An extract of B. serrata (34.2 mg/kg/day) was administered by oral gavage for 2 days before and after the induction of colitis with 4 mL of 4% AA. The anal sphincter pressure in the colitis group showed a significant decrease compared to that of the control groups (p < 0.001). The analysis of the values of lipid peroxidation (LPO) obtained by substances that react with thiobarbituric acid (TBARS) showed a significantly increased LPO in the colitis group compared to the control groups (p < 0.001). The nitric oxide levels and the expression of inducible nitric oxide synthase (iNOS) showed a significant increase in the colitis group compared to control groups (p < 0.01). Both pretreatment and treatment with B. serrata exhibited significantly reduced lipid peroxidation, nitric oxide and iNOS and showed improvements in tissue injury and anal sphincter pressure in animals with ulcerative colitis. The B. serrata extract has protective anti‐inflammatory and antioxidant effects that inhibit inflammatory mediators in acute experimental colitis. Copyright © 2014 John Wiley & Sons, Ltd.